Morphology and water absorption analysis on single fibre and Leaf of typha latifolia - Othman, MaizatulNisa; Ghazali, Ruzaidi; Khalid, Khalisanni; Zakaria, Nazarudin (Trans Tech publication, 2012)
The aim of this study is to determine the morphology and water uptake behaviour of single fibre and leaf of Typha Latifolia. In order to study the morphology and water uptake properties of the fibre, a single fibre was taken out from the Typha Latifolia leaf. The leaf was divided into two-part that are top and bottom parts. From direct observation towards leaves, the leaf at the bottom part has more cavities compare to the leaf on the top parts of the tree. Based to morphology analysis, the fibres were found randomly held in the middle of the top part and there were spongy structures in the middle of the bottom part of the leaves. SEM analysis evidenced that a single Typha Latifolia fibre is from a bulk of fibre. A water absorption result at top part of the leaf is higher than bottom part of the leaf with 79.79% and 66.63%, respectively. It was observed that different part of Typha latifolia could absorb water with different percentages.